PC Controller Switches - Mohamed Sutan, Norsuhaila (2004)
This thesis describes the developed hardware and software for PC Controller Switches. PC Controller Switches is the new approach in system control nowadays. By using the personal computer (PC), users can control the switch states of the devices in a room. In hardware implementation, a transmitter and a receiver are created to form a link between the computer and devices. The link is wireless and radio frequency is used as the technology to convey the control signal from PC to destination. In short words, the hardware is established in five states: Frequency Shift Keying (FSK) Modulator, Frequency Modulation (FM) Transmitter, FM Receiver, FSK Demodulator and Devices Interfacing. AH the states are combined together to operate as PC Control System. For software design, Visual Basic is used to develop the program that will control the devices. So the PC able to integrated with the hardware for control purpose. The written program must be able to send the control signal through serial port to integrated hardware.